We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
91
1
avatar+361 

If f(x) = x^2 and g(x) = x - 3, then f(g(x)) = ?

 Nov 29, 2018

Best Answer 

 #1
avatar+4827 
+1

\(f(x) = x^2\\ g(x) = x-3\\ f(g(x)) = f((x-3)) = (x-3)^2\)

.
 Nov 29, 2018
 #1
avatar+4827 
+1
Best Answer

\(f(x) = x^2\\ g(x) = x-3\\ f(g(x)) = f((x-3)) = (x-3)^2\)

Rom Nov 29, 2018

38 Online Users

avatar
avatar
avatar
avatar
avatar
avatar